Os Acromiale in Reverse Total Shoulder Arthroplasty: A Cohort Study. Issue 11 (24th November 2020) - Carpeggiani, Guilherme; Hodel, Sandro; Götschi, Tobias; Kriechling, Philipp; Bösch, Marco; Meyer, Dominik C.; Wieser, Karl
Background: Increased passive deltoid tension after reverse total shoulder arthroplasty (RTSA) potentially leads to displacement or tilting of a preexisting os acromiale. Purpose: To analyze patients with an os acromiale who underwent RTSA and compare their outcomes and complications with a matched control group without an os acromiale. Study Design: Cohort study; Level of evidence, 3. Methods: In this study, 45 shoulders in 42 patients with an os acromiale (cases) were matched to 133 patients without os acromiale (controls) who underwent RTSA between 2005 and 2016. The mean follow-up was 52 ± 32 months. Matching criteria included sex, type of surgery, duration of follow-up, and age. The Constant score (CS), Subjective Shoulder Value (SSV), and radiological outcomes were assessed postoperatively at 1-year, 2-year, and final follow-up visits. Results: The mean CS, SSV, and range of motion improved from preoperative levels to the final follow-up in both groups ( P < .01). Patients with an os acromiale had a relative CS of 70 ± 23 versus 76 ± 21 points ( P = .15) and an SSV of 70 ± 30 versus 73 ± 24 ( P = .52) compared with controls at the final follow-up visit. Patients with an os acromiale had significantly decreased active flexion of 104° ± 33° versus 114° ± 33° ( P = .03) at 1 year and active abduction of 103° ± 37° versus 121° ± 38° at 2 years postoperatively ( P = .02). A postoperatively painful os acromiale was found in 12 cases (27%) and spontaneously resolved in 8 cases after a mean of 33 months (range, 12-47 months; P = .04). Conclusion: RTSA reliably restores patient satisfaction despite the presence of an os acromiale, with a slightly impaired range of motion. Postoperative local tenderness at the os acromiale can be expected in 1 out of 4 patients, but this resolves spontaneously over time in the majority of patients.